2007
DOI: 10.1021/bc700307y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Maleimide Derivative of DOTA for Site-Specific Labeling of Recombinant Affibody Molecules

Abstract: Affibody molecules are a new class of small (7 kDa) scaffold affinity proteins, which demonstrate promising properties as agents for in vivo radionuclide targeting. The Affibody scaffold is cysteine-free and therefore independent of disulfide bonds. Thus, a single thiol group can be engineered into the protein by introduction of one cysteine. Coupling of thiol-reactive bifunctional chelators can enable site-specific labeling of recombinantly produced Affibody molecules. In this study, the use of 1,4,7,10-tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(159 citation statements)
references
References 27 publications
13
145
1
Order By: Relevance
“…Taking into account that the in vivo specificity study demonstrated that radioactivity uptake in these organs was saturable, we can conclude that this uptake was receptor specific. Previously, an affibody molecule with an unrelated specificity for Taq polymerase (ZTaq), which has the same 3-helix structure and that only differs in the few amino acids in the binding region, was tested for biodistribution and tumor uptake in LS174T xenograft model [20,22]. The level of radioactivity concentration in tumors due to unspecific uptake was lower or on the level of muscles and blood.…”
Section: In Vivo Comparison Of Biodistribution Of New (Hehehe-tagged)mentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account that the in vivo specificity study demonstrated that radioactivity uptake in these organs was saturable, we can conclude that this uptake was receptor specific. Previously, an affibody molecule with an unrelated specificity for Taq polymerase (ZTaq), which has the same 3-helix structure and that only differs in the few amino acids in the binding region, was tested for biodistribution and tumor uptake in LS174T xenograft model [20,22]. The level of radioactivity concentration in tumors due to unspecific uptake was lower or on the level of muscles and blood.…”
Section: In Vivo Comparison Of Biodistribution Of New (Hehehe-tagged)mentioning
confidence: 99%
“…Together with very high affinity, this permits high-contrast imaging of target expression within a few hours after injection. Multiple studies with different xenograft models have demonstrated that there is no unspecific uptake of affibody molecules in tumors, which is important to exclude false-positive findings [20,21,22]. Two clinical studies have confirmed the potential of affibody-based agents for imaging of HER2-expressing metastases in patients with disseminated breast cancer [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unlikely that 111 In and 68 Ga were released from the chelator. In addition, we have earlier directly compared an 111 In-labeled recombinant 3-helix Affibody molecule conjugated to maleimido DOTA through C-terminal cysteine with a synthetic counterpart conjugated to DOTA via an amide bond [40]. We have not found any significant difference in liver uptake between these two conjugates.…”
Section: Vivomentioning
confidence: 97%
“…In principle, uptake in these organs might be specific. However, a numerous studies with parental Z HER2:343 and its derivatives having the same binding site have demonstrated that uptake in these organs is not saturable, and therefore nonspecific [40][41][42][43][44]. Much lower uptake was also for radiolabeled PEP09239 having the same binding site and higher affinity to HER2.…”
Section: Vivomentioning
confidence: 99%
See 1 more Smart Citation